Carnivore intra-guild competition in Selati Game Reserve, Limpopo Province, South Africa - Comley, Jessica (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2020)
Carnivore intra-guild interactions can be important drivers of carnivore community composition and ecosystem functioning. Large carnivores are particularly important since they occupy the highest trophic levels and can exert extensive influences on subordinate carnivores and prey species. Given Africa's rapidly expanding human population, enclosed reserves such as those found in South Africa, may become increasingly important for carnivore conservation. A major concern, however, is that the interactions and co-existence of multiple carnivores in these systems is poorly understood. Additionally, the majority of reserves in South Africa are small ( 400kmÂ²), potentially increasing the likelihood of competition. My research aimed to provide insight into the interactions and co-existence of a multi-carnivore community within a small, enclosed reserve in South Africa (Selati Game Reserve). I tackled this task by using a combination of field techniques including camera trap surveys, ungulate transect surveys, aerial count surveys, location data collected from collared large carnivores and scat and kill site analyses. I found that carnivore-carnivore interactions, and their associated impacts, varied within the carnivore guild and that co-existence may be due to trade-offs between various risks (i.e. interference and exploitative competition) and benefits (i.e. resources such as food and space). My findings also revealed that large carnivores, such as lions (Panthera leo), spotted hyaenas (Crocuta crocuta) and leopards (Panthera pardus) do not have homogenous effects and that site-specific research on multiple-carnivores is integral for conserving biodiversity and ecosystem dynamics. Lions were the dominant large carnivore (in terms of intra-guild predation, space use and resource use) despite being outnumbered seven to one by spotted hyaenas. Leopard occupancy was negatively influenced by lions and leopard diet overlapped almost completely (91%) with spotted hyaenas, suggesting increased kleptoparasitism of leopard kills by spotted hyaenas. While my study provides valuable insight into the complexity of carnivore intra-guild competition in a small, enclosed reserve it also highlights major research gaps and emphasises the need for ecosystem-based research throughout southern Africa to fully understand how multiple sympatric carnivores co-exist in these systems.
Keywords: Hyenas -- Behavior -- South Africa; Hyenas -- South Africa; Hyenas -- Ecology -- South Africa; Top predators -- South Africa; Top predators -- Ecology -- South Africa; Animal communities -- South Africa; Animal behavior -- South Africa; Mutualism (Biology) -- South Africa; Coexistence of species -- South Africa; Game farms -- South Africa; Selati Game Reserve (South Africa)